Weight-balanced security-aware scheduling for real-time computational grid. (1st January 2011) - Kashyap, Rekha; Vidyarthi, Deo Prakash
Security-aware scheduling for real-time grid applications is an important task and a little work has been done to accomplish this. In this paper, we propose two scheduling algorithms for real-time grid applications with stringent security requirements, and the proposed algorithms are compared with a few existing scheduling algorithms, i.e. MinMin, MaxMin, EDF/ECT, SPMinMin and SPMaxMin. Security overhead computation for existing and proposed models is done on the basis of security level demand of the tasks. Performance of WB-EDFMin on success rate performance metric is considered to be the best among all the contemporary scheduling algorithms. SFWB-EDFMin compromises on the overall success rate of the grid application but its task scheduling is uniformly spread over the tasks of all security levels.